Dislocation after Posterior Stabilized Primary Total Knee Replacement: A Rare Complication in Four Cases - W. Spierenburg; E. L. A. R. Mutsaerts; J. J. A. M. van Raay (Case Reports in Orthopedics)
Introduction. Dislocation of a total knee arthroplasty is a rare complication that has rarely been described, while the total knee arthroplasty is frequently performed. From literature, we know patient-related factors, like obesity, neuropsychiatric disease, and severe valgus or varus deformity, are associated with higher risk of dislocation. We show our cases for awareness of the risk factors for surgeons. Case Presentations. We present four patients with a dislocation after a total knee arthroplasty. We compare these case reports with previous literature and show the most important risk factors for these dislocations. In our cases, three of them suffered from obesity, which possibly has contributed to the dislocation. Three patients did have instability which emphasizes the importance of ligament balancing while performing a total knee replacement. In all cases, an exchange of the polyethylene liner was performed. Conclusion. Implant-related factors and surgical technique as well as patient-related factors can contribute to this uncommon complication. Obesity, neuropsychiatric disorders, and a severe valgus or varus deformity are important patient-related risk factors. Our cases show these risk factors too. Some of these risk factors were encountered as well as other comorbidity factors. Such risk factors must be taken into consideration when deciding whether to perform a total knee arthroplasty. This stresses the importance of patient education and shared decision-making before performing a total knee replacement.